Signaling pathways in the epithelial origins of pulmonary fibrosis - Hardie, William D (Landes Bioscience, 2010)
Pulmonary fibrosis complicates a number of disease processes and leads to substantial morbidity and mortality. Idiopathic pulmonary fibrosis (IPF) is perhaps the most pernicious and enigmatic form of the greater problem of lung fibrogenesis with a median survival of three years from diagnosis in affected patients. In this review, we will focus on the pathology of IPF as a model of pulmonary fibrotic processes, review possible cellular mechanisms, review current treatment approaches and review two transgenic mouse models of lung fibrosis to provide insight into processes that cause lung fibrosis. We will also summarize the potential utility of signaling pathway inhibitors as a future treatment in pulmonary fibrosis. Finally, we will present data demonstrating a minimal contribution of epithelial-mesenchymal transition in the development of fibrotic lesions in the transforming growth factor-alpha transgenic model of lung fibrosis.